Hubungan Aktivitas Sosial, Pengetahuan Orangtua Tentang Kesehatan Reproduksi Dan Kontrol Orangtua Dengan Perilaku Seks Bebas Pada Remaja SMP Negeri 2 Sambirejo, Sragen - IDAWATI, EKA (2012)
Free sexin adolescentsis increasing andis a problemto be solved. This study aimstoprove the relationship of social activity ofparents, parental knowledge about reproductive health and parental controls with free sexbehaviorin adolescents at SMPN 2Sambirejo. This studyis an observational study with across sectional design. The subject of this study were students of grade 3 at SMP N 2Sambirejoand their parents. The population in this study were adolescents at SMP N 2Sambirejowith the status ofclass3 that as many as140students, with a sample of70 students. The sampling technique used was the simple random sampling. Statistical analysis used in this study is Correlation Pearson Product Moment with the confidence levelα=0.05.The results showed that there is a relationship between parental social activity significant p value=0.005 with a coefficient correlation value(r=0.332), parental knowledge about reproductive health p= 0.008withthe value of the coefficient correlation (r=-0.312 ), parental controls p=0.000 with the coefficient correlation (r=-0.455).